Synthesis and Characterization of Polyaniline/CuO Nanocomposites with Various Temperature - Risa Rahmawati Sunarya; Yosi Yosiva Sidik; Fitri Nur Islamiati (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
Polyaniline (PANI) metal oxide composites are known for their high electrical conductivity, environmental stability, and enhanced mechanical strength, making them valuable in applications such as sensors, batteries, and electromagnetic shielding. This study focuses on synthesizing and characterizing PANI/CuO nanocomposites to examine their structural, morphological, and functional properties at different synthesis temperatures. By integrating the conductive polymer PANI with copper oxide (CuO), a p-type semiconductor with a narrow band gap, the material’s capabilities are significantly enhanced. The oxidative polymerization of aniline, the process by which PANI is formed, requires precise control of oxidizing agents and reaction conditions, as these factors directly affect the polymerization, conductivity, and overall properties of the resulting nanocomposite. The PANI/CuO nanocomposites were synthesized at three different temperatures: 10℃, 25℃, and 50℃, to determine how temperature affects their characteristics. Fourier Transform Infrared (FTIR) spectroscopy and Scanning Electron Microscopy (SEM) were employed to analyze these nanocomposites. FTIR results revealed shifts in the quinoid and benzenoid rings, indicating hydrogen bonding between the NH group of PANI and the CuO surface, which accelerates charge transfer. The SEM analysis showed that while pure PANI exhibits a uniform globular morphology, the PANI/CuO nanocomposites display a nanorod morphology. These morphological differences impact the surface area and electrical conductivity of the composites, highlighting the significance of temperature in tailoring the material's properties for specific applications.